Theileria-transformed bovine leukocytes have cancer hallmarks - Tretina, Kyle; Gotia, H.T.; Mann, D.J.; Silva, Joana C. (Elsevier, 2015)
The genus Theileria includes tick-transmitted apicomplexan parasites of ruminants with substantial economic impact in endemic countries. Some species, including Theileria parva and Theileria annulata, infect leukocytes where they induce phenotypes that are shared with some cancers, most notably immortalization, hyperproliferation, and dissemination. Despite considerable research into the affected host signaling pathways, the parasite proteins directly responsible for these host phenotypes remain unknown. In this review we outline current knowledge on the manipulation of host cells by transformation-inducing Theileria, and we propose that comparisons between cancer biology and host–Theileria interactions can reveal chemotherapeutic targets against Theileria-induced pathogenesis based on cancer treatment approaches.